The correlation between exclusive breastfeeding and wasting in toddlers in the working area of Gisting Public Health Center, Tanggamus Regency - Viorena Hanes; Hikmah Ifayanti; Komalasari Komalasari (Science Midwifery, 2023)
One of the acute nutritional deficits, wasting, has a significant influence on toddlers' growth and development, increasing their risk of cognitive impairment and death. According to the Riskesdas Indonesia 2018 data, the prevalence of under-five malnutrition reached 10.2%. According to the examination of the nutrition program at the Gisting Public Health Center, wasting affected 11.9% of toddlers. The objective of this study was to determine the correlation between exclusive breastfeeding and wasting in toddlers in the working area of Gisting Public Health Center, Tanggamus Regency in 2022. This type of research is a quantitative study using an analytical survey method with a Case-Control approach. The population in this study was all toddlers in the Working Area of Gisting Public Health Center, Tanggamus Regency, Lampung in 2022. The data collection method used primary data using interview guidelines and secondary data using MCH books and cohorts. The sample for this study consisted of 356 participants who were split into 178 case groups and 178 control groups. This study used a straightforward random sample technique for sampling. The chi square test is the method of analysis. According to the study’s finding, exclusive breastfeeding and wasting are related (p-value 0.04<0.05). Suggestions for how the Gisting Health Center could educate moms of young children about the benefits of exclusive nursing in order to prevent wasting.